Hubungan Konsetrasi NO2 Udara Ambien Terhadap Konsentrasi NO2 Udara Dalam Ruang Di Lampu Merah Simpang Jelutung Kota Jambi - Peppy Herawati; Anggrika Riyanti; Ageng Pratiwi (Jurnal Daur Lingkungan, 2018)
ABSTRACTTtransportation is one of the factors that have a major influence in air quality decline. Air pollution is not only happening outside the room and will mobilization activities of motor vehicles, but it can affect air quality in space. One of the pollutant gas produced from vehicles is the concentration of Nitrogen Dioxide (NO2). This allows an exposure that will impact on public health. The purpose of this study is to determine the relationship of NO2 air ambient concentration (outdoor) to indoor air (indoor) in Simpang Jelutung Red Lights area. The method used in this study is quantitatif method. Data collection using sampling NO2 concentration in outdoor and indoor. The relationship between outdoor and indoor NO2 concentrations was analyzed using Pearson correlation. This is in line with the small influence of air NO2 concentration in space on public health. Result shows that all of the sample is still categorized either or not passing the air quality standard (150 μg / m3) in Government Regulation Number 41 Year 1999. The correlation analysis result  show relationship NO2 concentration between ambient air (outdoor) to indoor air was 13%, which means that correlation relationship is very weak.  Keywords:     Ambient air, indoor air, NO2 concentration